‘Matahari’ rises on UMP’s horizon - UMP, PNC
Over time, there has been a dramatic increase in the active involvement of women in the economic and administrative sectors, so much so, it demands this gender to become ever more prepared in meeting the challenges of the day, said Pahang’s Sultanah, Her Royal Highness Tunku Hajjah Azizah Aminah Maimunah Iskandariah Binti Almarhum Sultan Iskandar Al-Haj, at the launching ceremony of Universiti Malaysia Pahang’s (UMP) Women Association – fondly known as “MATAHARI” – at the university’s Sports Complex recently.